Application of Linear Light Source in New Media Performance - Yu Shen, Tian Yu, (Design Engineering, 2020)
Scientific and technological progress and media technology evolution have provided beneficial development environment for the field of art design [1]. The mode combining technology and art has been constantly updated and adopted in new media exhibition performance. Among them, linear light source has been extensively adopted in new media exhibition performance and reflected the charm of science and technology integration on account of its advantages such as high luminous efficiency, rich light source color, low energy consumption, long service life and flexible and convenient application. The development trend of new media exhibition performance puts forward new requirements for artistic practitioners in terms of creation ideas, creation methods and creation means. Interactive coding technology has provided strong support for the realization of media interaction, which can enable the viewers to experience richer viewing experience. The exhibition performance is no longer limited to the linear narrative mode. It has broken through the limitation of time and space in traditional exhibition performance and displayed varied artistic expression forms. The author found in the process of learning and practicing with the tutor that even though the application of linear light source in new media exhibition performance has been widely accepted with the extensive launching of light art festivals all around the world, many literature focus more on the case analysis of individual artists and some music festivals while the systematic and theoretical researches are relatively insufficient. This paper aims at summarizing the characteristics of linear light source and the development trend of new media exhibition performance by means of case analysis and literature review, conducts in-depth exploration in the application method and design principle of linear light source in new media exhibition performance by combining with the practical application experiences of linear light source in the research period, strives to figure out a method to realize the mutual balance between media technology and beauty in form, resolves the problem of the existence of the connection gap between practice and theory in terms of the application of linear light source in new media exhibition performance currently and provides theoretical basis and experimental and practice materials for reference.